Uso de tecnologias digitais no ensino e na aprendizagem de álgebra linear na perspectiva das teorias da aprendizagem significativa e dos registros de representação semiótica - Kripka, Rosana Maria Luvezute (2018)
This work deals with the identification and analysis of influences of technology resources use in teaching and learning of Linear Algebra, evaluated in the classroom context. The question used as a guideline for the reasearch was: “Considering the perspectives of Meaningful Learning and the Semiotic Representation Registers, in which way the teacher and the students perceive the use of digital technology resources, in classroom, related to the processes of teaching and learning that occur in the classes of Linear Algebra?” The research is a holistic multiple study case, characterized as naturalistic-constructive, with quantitative and qualitative approaches. The research had 61 students enrolled in Linear Algebra, from three different classes of Civil Engineering course that belong to a community university (IES) placed in Rio Grande do Sul, Brazil. The work was aimed at identifying and analyzing potentialities and weaknesses perceived by the students and the teacher involved in the learning and teaching Linear Algebra processes, related to the use of digital technologies resources, proposed in tasks elaborated and developed in the classroom context. The same didactic sequence was applied to the three different classes. In two of them, potentially meaningful tasks were applied to two classes, exploring the continuous use of digital technology resources such as geotechnologies and apps like GeoGebra, MATLAB and Excel spreadsheet. In the third classroom, the use of digital technology resources was explored in only one task. The gathering of data was done through observations, questionnaires, productions made by the research participants and the teacher's logbook. Mixed methods were considered in the analysis of data. Techniques of content analysis were used in the treatment of qualitative data and, for the quantitative data, descriptive analysis were carried out. The t tests were used for independent samples. We conclude that, although there was no significant statistical difference between the average scores of the analyzed groups, the perceptions about the continuous use of technological resources, in the didactic proposal elaborated, indicated that there were increases in the frequencies of identification of understanding of concepts as well as in the significant learning in the discipline; the use of digital technologies favored the processes of teaching and learning in Linear Algebra, facilitating the pedagogical mediation, the understanding and the construction of mathematical concepts; and the continued use of technologies is more favorable than timely use, since familiarization with the use of technological resources, for the purpose of knowledge construction, is necessary and needs a longer time for its adequacy.